Reducing risk, strengthening resilience: Social protection and nutrition - Drimie, Scott; Yosef, Sivan (International Food Policy Research Institute, 2016)
IN THE MID-1990S, governments and researchers in three countries from very different parts of the world—Bangladesh, Brazil, and Mexico— began moving toward a new type of poverty alleviation program. Struggling to meet the needs of their poor populations through various poverty-reduction initiatives, they wondered whether attaching conditions to those programs would make a difference. What if in exchange for receiving a food basket or a cash voucher, program beneficiaries were asked to, for example, bring their infants to the local health clinic for growth monitoring, or enroll their older children in secondary school? Such a change could not only meet the immediate needs of citizens, but also help improve their longer- term welfare and development, all of which affect nutrition.